Uji Efektivitas Berbagai Konsentrasi Jenis Nutrisi Alternatif Terhadap Produksi Jamur Tiram Putih (Pleurotus ostreatus) di Kabupten Karawang - Rommy Andhika Laksono; Fawzy Muhamad Bayfurqon; Miftakhul Bakhrir R.K (Paspalum: Jurnal Ilmiah Pertanian, 2018)
In the development of modern agriculture based on location specification agriculture, to increase the production of white oyster mushrooms, requires able to utilize alternative natural resources that are easy to obtain and efficient.The research was conducted with the aim to study and get the concentration of alternative nutrient types that can provide the highest production of white oyster mushroom in Karawang regency. Based on the purpose, this research is verifikatif.The method used is experimental method and experiment design used is single factor randomized block design (RAK) consisting of 17 treatments in 3 repetitions : A (100% Aquades Concentration); B (20% Leri Water Concentration); C (40% Leri Water Concentration); D (60% Leri Water Concentration); E (80% Leri Water Concentration); F (20% Potato Skin Extract Concentration); G (40% Potato Skin Extract Concentration); H (60% Potato Skin Extract Concentration); I (80% Potato Skin Extract Concentration); J (20% Bean Sprouts Extract Concentration); K (40% Bean Sprouts Extract Concentration); L (60% Bean Sprouts Extract Concentration); M (80% Bean Sprouts Extract Concentration); N (20% Old Coconut Water Concentration); O (40% Old Coconut Water Concentration); P (60% Old Coconut Water Concentration); Q (80% Old Coconut Water Concentration). The effect of treatment was analyzed by F test of 5% level and if significant, then to know the best treatment was continued with Duncan Multiple Range Test at 5% real level.The results achieved from this research is the application of various types of concentrations of alternative nutrients have a real effect on total clumps per baglog, total hood per clumps, maximum hood diameter per baglog, harvest intensity per baglog, dry weight of mushrooms per baglog, and fresh weight of mushrooms per baglog white oyster mushroom in Karawang regency. 80% concentration of leri water is able to give the highest growth and yield of white oyster mushroom in Karawang regency, with fresh weight of mushroom reach 142,35 gr per baglog per week or 0,85 tons per 1000 baglog in one plant period (6 MSA).